2019
DOI: 10.1177/0036850419892190
|View full text |Cite
|
Sign up to set email alerts
|

Application of piezoelectric actuator in series nano-positioning stage

Abstract: The existing nano-positioning stages are driven by the piezoelectric ceramics, which have features of high accuracy and resolution, but the traditional positioning stage could not meet the requirement of large working space because the displacement of the piezoelectric ceramics is only tens of microns. To solve the contradiction between high accuracy and large working space, a novel non-resonant piezoelectric linear actuator, which adopted the two parallel v-shaped stators as the double driving feet, was propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The linear correlation between the temperature and tan θ tem indicated a thermal-induced resolution of 0.00073°/°C (12.7 μrad/°C). As far as piezoelectric-driven rotary module is concerned, compared with existing piezoelectric-driven rotary actuators with excellent rotation resolutions, including ultrasonic rotary table (0.24 μrad), inchworm type actuator with the changeable clamping radius (0.25 μrad), planar actuator through bending–bending hybrid mode (0.198 μrad), 3 degrees of freedom stage with T-shape flexure mechanism (0.3 μrad), and nonresonant nanopositioning stage (0.3 μrad), the piezoelectric-driven rotary module achieved a considerable level of resolution, as a rotation resolution of 0.2 μrad was obtained. Therefore, the coupling driven performances involving superior macroscopic and microscopic resolutions were experimentally revealed.…”
Section: Resultsmentioning
confidence: 99%
“…The linear correlation between the temperature and tan θ tem indicated a thermal-induced resolution of 0.00073°/°C (12.7 μrad/°C). As far as piezoelectric-driven rotary module is concerned, compared with existing piezoelectric-driven rotary actuators with excellent rotation resolutions, including ultrasonic rotary table (0.24 μrad), inchworm type actuator with the changeable clamping radius (0.25 μrad), planar actuator through bending–bending hybrid mode (0.198 μrad), 3 degrees of freedom stage with T-shape flexure mechanism (0.3 μrad), and nonresonant nanopositioning stage (0.3 μrad), the piezoelectric-driven rotary module achieved a considerable level of resolution, as a rotation resolution of 0.2 μrad was obtained. Therefore, the coupling driven performances involving superior macroscopic and microscopic resolutions were experimentally revealed.…”
Section: Resultsmentioning
confidence: 99%
“…Alghanmi et al [16] analysed bending behaviour of the FG plates integrated with Piezoelectric fibre reinforce composite (PFRC) materials and concluded that maximum deflection occurred when PFRC actuator is attached at surface of porous FG plate. Some other related studies focus on the application of piezoelectric material used in smart structures [17][18][19][20]. It is observed from the review of literature that bending and vibration studies of smart beams made of CNT reinforced FG materials are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them operate only as linear type, rotational type, or can move itself in the plane. In order to combine two types of motion into one piezoelectric system, several piezoelectric actuators must be composed, and the aforementioned disadvantages will be met again [15,16]. Therefore, the objective of this research is to develop a multi-DOF locomotion type piezoelectric actuator consisting of a single transducer that is able to provide unlimited self-motion in the plane and rotate spherical payload.…”
Section: Introductionmentioning
confidence: 99%